Cytogenetic effects of medicinal plants for diabetes mellitus on human leukocytes cultured in vitro - Mendioro, M. S. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
Aqueous extracts from the bark of Syzygium cumini L. (locally, duhat) and leaves of Artemisia vulgaris L. (damong Maria) and Catharanthus roseus L. (chichirica), and tablets of Momordica charantia L. (ampalaya) were tested on human leukocytes cultured in vitro. All four medicinal plants were found to be possible mutagens. Mean mitotic indices of the leukocytes were reduced significantly by S. cumini, A. vulgaris and C. roseus as the concentrations of treatments were increased. M. charantia tablets did not significantly affect the mitotic index. Loose sister chromatids, gaps and breaks were the chromosomal abnormalities observed. Chromosomal aberration was 36.0% for A. vulgaris leaves, 79.0% for C. roseus leaves and 81.00% for S. cumini bark. A. vulgaris, C. roseus and M. charantia significantly induced chromosome condensation.